A guardiã de minha irmã, de Jodi Picoult: diálogos entre a literatura e o direito no romance e sua adaptação para o cinema - Dallazen, Clariane Leila (2019)
This research has as corpus of analysis the best-selling novel My Sister's Keeper (2003), translated into Portuguese as A guardiã da minha irmã (2011) and adapted to the movies as “My sister’s keeper” (2009). This novel is considered a marketing novel. Based on the assumptions of Comparative Literature and its possibilities of dialoguing with other areas of knowledge, the present research starts from the theory of focalization and intertextuality to analyze the mentioned narratives, in order to understand how the process of adaptation to the cinema occurs, establishing distances and approximations. From this point we go on analyzing how the thematic of the freedom to exercise the law to die works in the mentioned pieces of art. Therefore, we start our analysis with the narrative focus presented in the book and its representations. Following the course, we look for approximations and distances between the book adapted to cinema, appointing the intertextual dialogues between both pieces of art. We also establish dialogues between Literature and Law, once we talk about death and freedom of the exercise of this law, passing through the difficulties inherent the acceptance of the inevitability of death, as well as of the alea itself to be alive. Our theoretical framework includes studies by Carreira (2015), Alós (2012), Camarero (2008), Carvalhal (2006), Kristeva (2005), Guillém (2005), Nitrini (1997), Wellek (1994), Mendoza Fillola (1994), concerning Comparative Literature. Afterwards, Lubbock (1976) and Leite (1989) are going to orientate our comprehension of the difference in the composition of a scene and a summary, in the narrative construction. Their assumptions are followed by the ones by Friedmann (2002), who is going to orientate, by its time, our comprehension of the modalities and positions held by the narrator, being also supported by Leite (1989), Genette (1972), Massaud Moisés (1985) and Gomes (2002). In relation to the focalization, our base is set upon Reis and Lopes (1988), Brandão (2013), Sá (2012), Bulhões (2009), Andrade and Ponte (2012), Cardoso (2013), and Sotta (2015). With this theoretical framework, under others, this research allowed us to understand how the different languages used by Literature and Cinema can produce distinct meaning effects which are, at last, related to the destined public of every one of the ways of enunciation. They establish an individual dialogue with the reader who, by its time, wakes up to a reflection concerning a relevant social and juridical theme: the liberty\freedom of choosing to live or to die along a life in which death is more than inevitable but eminent.